Capability of Rice Husk Silica on Flexural Improvement in Metal Ceramic Restoration - Sopan Sinamo; Mourent Miftahullaila; Hendrik Steven (HM Publisher, 2022)
Background: Metal ceramic restoration (MCR) is a gold standard due to its ability to withstand masticatory forces and aesthetics. However, it frequently appears to experience a fracture in the oral cavity. The ceramics in MCR consist of an opaque dentin and enamel layer, which contain silica to give the ceramic strength. Silica is an abundant material, mainly synthesized from rice husks. The study was aimed to investigate the effect of silica added to commercially opaque porcelain powder in increasing the flexural strength of MCR. Methods: The research sample was rectangular Co-Cr metal [(25±1) mm × (3±0.1) mm × (0.5 ± 0.05) mm], and opaque porcelain powder and dentin [(8±0.1) mm× (3±0.1) mm ×(1.1±0.1) mm]. White silica powder was synthesized from rice husk by sonication for 270 minutes, characterized by x-ray fluorescence (XRF). Silica was mixed with commercial opaque porcelain powder with various concentrations of 0, 0.5, and 1%, porcelain coating procedure on the centre of the surface metal, followed by sintering at 9500C. Results: Characterization with XRF showed that the elemental content of pure silica was 83.9%. The average flexural strength value with three-point bending in each sample is 109.67±12.163; 131.26±3.817; and 108.35±4.26. The results of statistical tests using One Way ANOVA stated a significant increase in the flexural strength of MCR (p<0.05) post added the rice husk silica to the commercial opaque porcelain powder. Conclusion: Adding 0.5% silica resulted in the optimal flexural strength of MCR.